Symbiotic Modulation as a Driver of Niche Expansion of Coastal Plants in the San Juan Archipelago of Washington State - Redman, Regina S.; Anderson, Joe A.; Biaggi, Taylor M.; Malmberg, Katie E. L.; Rienstra, Melissa N.; Weaver, Jamie L.; Rodriguez, Rusty J. (Frontiers in Microbiology, 2022)
Modern evolutionary theory and population genetics posit that adaptation and habitat expansion of plants result from processes exclusive to their genomes. Here, we present studies showing that plants can grow across complex habitat gradients by modulating symbiotic associations with Class 2 fungal endophytes. Endophyte analysis of three native (Leymus mollis, Distichlis spicata, Salicornia pacifica) and one invasive (Spartina anglica) plant growing across adjacent microhabitats in the San Juan Archipelago, altered associations with Class 2 fungal endophytes in response to soil salinity levels. At the microhabitat interfaces where the gradation of salinity varied, the plants were colonized by endophytes from both microhabitats. A reciprocal transplant study along a salt gradient demonstrated that Leymus mollis (dunegrass) required endophytes indigenous to each microhabitat for optimal fitness and/or survival. In contrast, when dunegrass and Grindelia integrifolia (gumweed) were found growing in low salinity, but high drought habitats, these plant species had their own unique dominant endophyte association regardless of geographic proximity and conferred drought but not high salt stress tolerance. Modulation of endophyte abundance occurred in planta based on the ability of the symbiont to confer tolerance to the stress imposed on plants. The ability of an endophyte to confer appropriate stress tolerance resulted in a significant increase of in planta fungal abundance. Conversely, the inability of an endophyte to confer stress tolerance resulted in a decrease of in planta fungal abundance. Our studies indicate that Class 2 fungal endophytes can provide a symbiotic mechanism for niche expansion and phenotypic plasticity across environmental gradients.